PENINGKATAN HASIL BELAJAR MELALUI PEMBELAJARAN DARING VIRTUAL DENGAN MEDIA/PLATFORM GOOGLE CLASSROOM PADA MASA PANDEMI COVID-19 - MOSES RIKU (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The writing of this best practice aims to describe improving student learning outcomes through virtual online learning with the Google Classroom media/platform during the Covid-19 pandemic. The subject of this best practice writing is the students of class X IPA SMA Negeri 1 Wolowae for the academic year 2020/2021 totaling 24 people consisting of 6 boys and 18 girls. The writing of this best practice uses a descriptive method by collecting information on student learning outcomes using the technique of giving tests. The learning strategy carried out in virtual online learning with the Google Classroom media/platform consists of six stages which include: (1) preparation of the Learning Implementation Plan (RPP); (2) preparation of learning modules/materials and Student Worksheets (LKPD); (3) uploading learning modules/materials and Student Worksheets (LKPD) to students via the Google Classroom media/platform; (4) the implementation and execution of learning tasks by students; (5) uploading and re-sending of learning results/tasks by students via the Google Classroom media/platform using mobile phones or laptops/PCs; and (6) examination of student learning outcomes / learning assignments accompanied by providing feedback. The implementation of virtual online learning with the Google Classroom media/platform during the Covid-19 pandemic can improve the learning outcomes of class X science students at SMA Negeri 1 Wolowae. In learning with Atomic Theory material, student learning outcomes increased from 70.83% in the initial learning to 87.50% with virtual classroom learning using the Google Classroom media/platform. This shows that there is an increase in student learning outcomes by 16.67%. Therefore, virtual classroom learning using the Google Classroom media/platform can be a solution and is one of the learning alternatives during the Covid-19 pandemic. ABSTRAKPenulisan best practice ini bertujuan untuk mendeskripsikan peningkatan hasil belajar siswa melalui pembelajaran daring virtual dengan media/platform Google Classroom pada masa pandemi Covid-19. Subjek penulisan best practice ini adalah siswa kelas X IPA SMA Negeri 1 Wolowae tahun pelajaran 2020/2021 berjumlah 24 orang yang terdiri dari 6 orang laki- laki dan 18 orang perempuan. Penulisan best practice ini menggunakan metode deskriptif dengan pengumpulan informasi hasil belajar siswa menggunakan teknik pemberian tes. Strategi pembelajaran yang dilakukan dalam pembelajaran daring virtual dengan media/platform Google Classroom terdiri dari enam tahapan yang meliputi: (1) penyiapan Rencana Pelaksanaan Pembelajaran (RPP); (2) penyiapan modul/bahan pembelajaran dan Lembar Kerja Peserta Didik (LKPD); (3) pengunggahan modul/bahan pembelajaran dan Lembar Kerja Peserta Didik (LKPD) kepada peserta didik melalui media/platform Google Classroom; (4) pelaksanaan dan pengerjaan tugas-tugad pembelajaran oleh peserta didik; (5) pengunggahan dan pengiriman kembali hasil /tugas pembelajaran oleh siswa melalui media/platform Google Classroom menggunakan handphone ataupun laptop/PC; dan (6) pemeriksaan hasil belajar /tugas pembelajaran peserta didik disertai pemberian umpan balik. Implemantasi pembelajaran daring virtual dengan media/platform Google Classroom pada masa pandemi Covid-19 dapat meningkatkan hasil belajar siswa kelas X IPA SMA Negeri 1 Wolowae. Pada pembelajaran dengan materi Teori Atom diperoleh hasil belajar siswa meningkat dari 70,83 % pada pembelajaran awal menjadi 87,50 % dengan pembelajaran kelas virtual menggunakan media/platform Google Classroom. Hal ini menunjukkan bahwa terjadi peningkatan hasil belajar siswa sebesar 16,67%. Oleh karena itu pembelajaran kelas virtual menggunakan media/platform Google Classroom dapat menjadi solusi dan merupakan salah satu aternatif pembelajaran selama masa pandemi Covid-19.